Synthesis, molecular docking and molecular dynamics studies of novel tacrine-carbamate derivatives as potent cholinesterase inhibitors - Ozten, Ozge; ZENGİN KURT, BELMA; ZENGİN KURT, BELMA; Sonmez, Fatih; Dogan, Berna; Durdagi, Serdar (My University, 2021)
© 2021 Elsevier Inc.In the present study, new tacrine derivatives containing carbamate group were synthesized and their acetylcholinesterase (AChE) and butyrylcholinesterase (BuChE) inhibition activities were evaluated. All synthesized compounds inhibited both cholinesterases at nanomolar level. Among them, ((1,2,3,4-tetrahydroacridin-9-yl)amino)ethyl(3-nitrophenyl) carbamate (6k) showed the best inhibitor activity against AChE and BuChE with IC50 value of 22.15 nM and 16.96 nM, respectively. The calculated selectivity index revealed that the synthesized compounds (exclude 6l) have stronger inhibitory activity against BuChE than AChE. The most selective compound was 2-((1,2,3,4-tetrahydroacridin-9-yl)amino)ethyl(4-methoxyphenyl)-carbamate (6b) with the selectivity index of 0.12. Molecular modeling approaches were employed to understand the interaction between the synthesized compounds and proteins. As carbamate derivatives can act as pseudo-irreversible inhibitors of AChE and BuChE, covalent docking approaches was applied to determine the binding modes of novel compounds at binding sites of cholinesterase enzymes.